2020
DOI: 10.1208/s12249-020-01840-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Borneol on the Release of Compound Danshen Colon-Specific Osmotic Pump Capsule In Vitro and Pharmacokinetics Study in Beagle Dogs

Abstract: Borneol can enhance the bioavailability of several other drugs by opening the bloodbrain barrier and inhibiting P-glycoprotein (P-gp) efflux. However, whether borneol will impact the bioavailability and the mechanism of compound Danshen colon-specific osmotic pump capsule (CDCOPC) remains unclear. This study aimed to determine the effects of borneol on the in vitro release and in vivo pharmacokinetic characteristics of CDCOPC. Besides, the in vitro release behavior of CDCOPC was further assessed by chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Similarly, Notoginsenoside R1 (NTR1), a tetracyclic triterpene present in the root of the popular Chinese medicine Panax ginseng [ 86 ], has been shown to inhibit the accumulation of Aβ in APP/PS1 mice and N2a-APP695sw cells, at least in part by activating the PPARγ pathway to increase IDE expression [ 87 ]. Meanwhile, it has been reported that ginsenoside Re and NTR1 exhibit improved bioavailability across the BBB when coadministered with Borneol [ 88 ]. Astragaloside IV (AS-IV), a tetracyclic triterpene from Astragalus membranaceus [ 89 ], has also been shown to be beneficial in neurodegenerative diseases with cognitive impairment [ 90 ].…”
Section: Mechanism Of Saponins In Treating Alzheimer’s Diseasementioning
confidence: 99%
“…Similarly, Notoginsenoside R1 (NTR1), a tetracyclic triterpene present in the root of the popular Chinese medicine Panax ginseng [ 86 ], has been shown to inhibit the accumulation of Aβ in APP/PS1 mice and N2a-APP695sw cells, at least in part by activating the PPARγ pathway to increase IDE expression [ 87 ]. Meanwhile, it has been reported that ginsenoside Re and NTR1 exhibit improved bioavailability across the BBB when coadministered with Borneol [ 88 ]. Astragaloside IV (AS-IV), a tetracyclic triterpene from Astragalus membranaceus [ 89 ], has also been shown to be beneficial in neurodegenerative diseases with cognitive impairment [ 90 ].…”
Section: Mechanism Of Saponins In Treating Alzheimer’s Diseasementioning
confidence: 99%